Kontruksi Hukum Pembebasan Pajak Penghasilan Terhadap Peralihan Hak Atas Tanah Dalam Pembagian Hak Bersama Waris - Misbah Imam Soleh Hadi; Bayu Indra Permana (Jurnal Ilmu Kenotariatan, 2022)
Tax as a source of state revenue play an important role in the life of the state, especially in development, so taxpayers in carrying out their obligations must be given definite legal guarantees by the state. However, this is not reflected in the regulation on the exemption of income tax on the transfer of land rights by sharing rights with inheritance, because the heirs must continue to pay income tax, so they are burdened with double taxes. This is because the regulations in the law and its implementing regulations do not provide firm legal certainty, therefore, to overcome these problems, it is important to find an ideal legal construction in setting the income tax exemption. This study uses a normative juridical method, with a legal approach and a conceptual approach. The results of the research carried out are that there is a vagueness of norms in the regulation of income tax exemption in inheritance, besides that there is also a gap in norms related to the criteria for acceptance and rejection of applications for the issuance of SKB PPh. So that the author provides an option for future arrangements related to the exemption of income tax on the transfer of land rights in inheritance, especially the distribution of joint rights, which is expected to provide benefits and a sense of justice for the heirs. KEYWORDS: Legal Certainly, Income Tax, Transfer of Land Rights, Inheritance.